9 Takotsubo cardiomyopathy: a single centre review from beaumont hospital experience. (5th October 2017) - Traynor, B; Voon, V; McAdam, BF
Abstract : Introduction: Takotsubo cardiomyopathy (TC) has now gained recognition as an independent cardiovascular disease process. It typically presents as suspected acute coronary syndrome (ACS) with an emotional stressor as a precipitant. Several diagnostic criteria have been suggested, of which, those published by the Mayo Clinic (2004, revised 2008) are most widely accepted, requiring temporal resolution of left ventricular regional wall motion abnormalities (RWMA) and the absence of obstructive coronary artery disease (CAD), myocarditis and phaeochromoctyoma. Aim: We studied the cohort of patients diagnosed with TC in our centre between 2010–2016. We reviewed the clinical and diagnostic data and reviewed patient outcomes with follow-up. Methods: This is a retrospective analysis of patients discharged from Beaumont Hospital with this diagnosis, as coded by HIPE data, between 01/2010 and 12/2016 by chart and electronic records review. 31 cases were identified but 11 of these patients were excluded as they had been incorrectly coded. These cases included dilated cardiomyopathy (n=3), tachycardia-induced cardiomyopathy (n=2), restrictive cardiomyopathy (n=1), intracranial haemorrhage (n=1). There was one case of myocarditis confirmed on CMR and one case of NSTEMI in a 34 year-old female who had severe LAD related infarction diagnosed on CMR. Of note, one patient, with a confirmed diagnosis, presented with TC on two separate occasions within three years. Data were expressed as mean ± SD and %. Results: The average age of this cohort was 64 ± 12 years, 90% were female and left ventricular ejection fraction at presentation was 34 ± 9%. All 20 patients had elevated Troponin I with peak level 3.13 ± 2.42 ng/ml. Coronary angiography was performed in all cases and showed no or minor CAD (n=18), 2 had moderate CAD. Classical antero-apical hypokinesis in the LAD territory was observed in all 20 patients. Follow-up imaging with either TTE, CMR or both was performed in 85% (n=17), all of which showed temporal resolution of RWMAs. 1 patient awaits scheduled repeat imaging and 2 patients were lost to follow-up. CMR was performed in 60% (n=12) of cases during initial presentation. Average length of stay was 21.2 ± 52 days and there were no inpatient deaths. There was no clinical indication to assess for phaeochromocytoma in our cohort. Conclusions: The number of cases of TC, as derived from HIPE data, seems small and had errors. We are cross-referencing our data with our cath lab database. In our small cohort, most subjects were female and all presented with classical findings. Our results confirm that a multimodality imaging approach, including early coronary angiography, is essential to ensure accurate and early diagnosis. Moreover, we found that early CMR is very helpful in the diagnosis and management of this interesting condition.